SEBARAN LOKAL ECHINODERMATA DI PANTAI BAMA TAMAN NASIONAL BALURAN - Vendi Eko Susilo (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2016)
The aims this reseach to determine the Echinodermata distribution in Bama Beach Baluran National Park. Quadrate transect method was used to collect the data. Substrat and number of species analisys with Software R 2.11.0. The results of this study, the sample Echinodermata obtained amounted to 255 individuals that consist of four Class is Asteroidea which consists of three species (Linckia laevigata, Archaster typicus, Echinaster callosus), Ophiuroidea teridiri of one species (Ophioderma sp.), Echinoidea consists of 3 species (Tripneustes sp., Diadema sp., Echinodiscus sp.) and Class Holothuroidea consists of three species, namely (Euapta sp., Holothuroidea sp., Holothuria argus). Keywords: Echinodermata, Bama Beach